“PENGEMBANGAN KARIR DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT XYZ” - Dedi Rianto Rahadi; Claudia Ocktaliani (President University, 2019)
Performance is the result of quality and quantity of work that can be achieved by an employee in carrying out tasks in accordance with the responsibilities given to the employee. Discipline is the most important operative function of human resource management because the better employee discipline is, the higher work performance can be achieved. Employees' career development is based on their own desires and efforts to train and develop themselves in relation to their work or position. The research aims to analyze the effect of work development, work discipline, job satisfaction and employee performance. The research respondents were employees of PT. XYZ, with a total of 150 respondents. The research method is path analysis and data collection through questionnaires. The results showed that career development on job satisfaction was significant, the effect of work discipline on job satisfaction was not significant. Career development on employee performance is significant and work discipline on employee performance is significant. Suggestions for PT. XYZ who are the object of this study in particular need to supervise the performance discipline of some career development in increasing job satisfaction and employee performance.Keywords: Career Development, Work Discipline, Job Satisfaction and Performance